IMPLEMENTASI FUZZY LOGIC CONTROL UNTUK VOLUME LARUTAN pH UP DAN pH DOWN PADA AKUAPONIK DENGAN METODE SUGENO - Muhammad Bismar Hamdan Effendi; Bambang Siswojo; Eka Maulana (Jurnal Mahasiswa TEUB, 2023)
Water quality is one of the main parameters in the aquaponic cultivation of tilapia and mustard greens. To produce tilapia and mustard greens that are healthy and fresh, the condition of the water in the aquaponics system must be maintained, one of which is the pH of the water. Tilapia and mustard greens require a pH range of 6 to 7, which is the optimal pH range for the growth of tilapia and mustard greens. Changes in the pH of aquaponic cultured water can adversely affect the lives of tilapia and green mustard, either directly or indirectly. Controlling the pH of water in aquaponic cultivation using the Sugeno fuzzy logic method involves determining the membership function so that it can control the administration of pH up (alkaline) and pH down (acidic) solutions. From the results of the study, the tool is able to control the pH of aquaponic aquaculture water according to the setpoint membership function that has been set, namely 6-7, and in several volumes of aquaponic cultivation ponds with a solution output of pH up and pH down according to the desired pH of aquaponic cultivation ponds with an error of 2.7%.Keywords: pH, Fuzzy Logic Sugeno, Membership Function, Volume, pH Up, pH Down